Design Learning Trajectory for Understanding the Concept of Fractions in ADHD Students (Attention Deficit Hyperactivity Disorder)with Realistic Mathematical Approach - Panggabean, Ellis Mardiana; Harahap, Tua Halomoan; Sitorus, Niken Ananda; Putri, Tiara Zakiah (JMEA : Journal of Mathematics Education and Application, 2025)
ABSTRACTLearning mathematics does not only depend on the material being taught, but also on how the source of the material is provided/delivered and how it is delivered. The low interest in learning mathematics and the difficulty in understanding formulas result in many children being less interested in learning mathematics. The lack of innovative learning media brought by teachers, the use of cellphones for online games makes students rarely open their textbooks. The design of the right learning path can be one of the factors for a teacher's success in carrying out learning activities. The use of the right learning path that has been planned by the teacher is also a factor that can trigger the enthusiasm for reading, thinking and analyzing the material being taught. The design of an effective and efficient learning path functions so that the learning objectives and ability indicators expected of students can be achieved optimally.The ability to understand the concept of addition and subtraction in fraction material is a basic thing that is important for all students, including students with attention and hyperactivity disorders known as Attention Deficit Hyperactivity Disorder (ADHD). This study uses a design research method consisting of three stages: the preparation stage, the two-cycle experimental stage (cycle I: initial experiment, cycle II: teaching experiment), and the retrospective analysis stage. Data collection was carried out through observation, interviews, initial tests, written tests, documentation, and field notes. The application of learning by carrying out real activities and directly witnessing the process of dividing Pizza into several parts makes students understand and be more enthusiastic in solving the questions provided by the researcher. Finally, after a series of research methods carried out, the researcher obtained research results that showed that learning activities designed by creating learning paths and media can actually help students understand the concept of addition and subtraction of fractional numbers. Indicators of conceptual understanding that emerged include the ability to classify objects, present concepts in the form of mathematical representations or images, develop conditions that are necessary and sufficient for a concept, use certain procedures, and apply concepts in problem solving. Finally, a learning path involving two activities with a realistic mathematical learning context supports understanding the concepts of addition and subtraction of fractions.